Clinical Application Study of Minimally Invasive Double-Reverse Traction in Complex Tibial Plateau Fractures. (22nd January 2022) - Cao, Faqi; Xue, Hang; Yan, Chenchen; Lin, Ze; Mi, Bobin; Panayi, Adriana C.; Xia, Tian; Zhou, Wu; Li, Hui; Liu, Guohui
Abstract : The aim of this study was to evaluate the clinical application of double-reverse traction for minimally invasive reduction of complex tibial plateau fractures. A retrospective analysis was performed to identify all patients admitted to the Department of Orthopedics, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, from March 2017 to December 2019 with Schatzker type VI tibial plateau fractures. 12 patients were identified (7 men and 5 women) with an average age of 46.15 ± 13 (39-58) years old. All patients were treated with double-reverse traction and closed reduction. After the fracture was reduced, the bone plate was fixed by percutaneous minimally invasive implantation. Outcomes assessed in this study include operation time and intraoperative blood loss. Imaging was performed during the postoperative follow-up, and functional recovery was evaluated at the final follow-up according to the Hospital for Special Surgery (HSS) score and the International Knee Joint Literature Committee (IKDC) functional score. Patients were followed up for 12.54 ± 1.5 (8-15) months. The average operation time was 63.63 ± 21 (35-120) minutes, and the average intraoperative blood loss was 105.45 ± 21 (60-200) mL. The Rasmussen imaging score was either excellent or good in all cases. The knee joint HSS score was 86.15 ± 6 (79-90) points, and the IKDC score was 80.01 ± 11 (75-90) points. No complications, such as wound infection, incision disunion, loosening of internal fixation, and internal fixation failure, occurred. In the treatment of Schatzker VI type complex tibial plateau fracture, the dual-reverse traction minimally invasive technique has the advantages of safety and effectiveness, less soft tissue injury, and allowing early joint movement, which is worthy of clinical promotion.